Early and Late Mortality Predictors in Patients with Acute Aortic Dissection Type B - Ratko M. Lasica; Jovan P. Perunicic; Dejana R. Popovic; Igor B. Mrdovic; Ross A. Arena; Nebojsa L. Radovanovic; Mina R. Radosavljevic-Radovanovic; Lazar D. Djukanovic; Milika R. Asanin (Cardiology Research and Practice)
Background/Aim. Despite technological advances in diagnosis and treatment, in-hospital mortality with acute aortic dissection type B is still about 11%. The purpose of this study was to assess the risk factors for early and long-term adverse outcomes in patients with acute aortic dissection type B treated medically or with conventional open surgery. Methods. The present study included 104 consecutive patients with acute aortic dissection type B treated in our Center from January 1st, 1998 to January 1st, 2007. Patient demographic and clinical characteristics as well as in-hospital complications were reviewed. Univariate and multivariate testing was performed to identify the predictors of in-hospital (30-day) and late (within 9 years) mortality. Results. 92 (88.5%) patients were treated medically, while 12 (11.5%) patients with complicated acute aortic dissection type B were treated by open surgical repair. In-hospital complications occurred in 35.7% patients, the most often being acute renal failure (28%), hypotension/shock (24%), mesenteric ischemia (12%), and limb ischemia (8%). The in-hospital mortality rate was 15.7% and the 9-year mortality rate was 51.9%. Independent predictors of early mortality in patients with acute aortic dissection type B were uncontrolled hypertension (HR-20.69) and a dissecting aorta diameter >4.75 cm (HR-6.30). Independent predictors of late mortality were relapsing pain (HR-7.93), uncontrolled hypertension (HR-7.25), and a pathologic difference in arterial blood pressure (>20 mmHg) (HR-5.33). Conclusion. Knowledge of key risk factors may help with a better choice of treatment and mortality reduction in acute aortic dissection type B patients.